Institutional Mechanics for the Advancement of Women - Sobritchea, Carolyn I. (Review of Women's Studies; Vol 25 No 1-2 (2015): Review of Women's Studies Volume XXV, Numbers 1-2 (January-December 2015), 2018)
Strategic Objectives H.1. Create or strengthen national machineries and other governmental bodies; H.2. Integrate gender perspectives in legislation, public policies, programmes and projects; H.3. Generate and disseminate gender-disaggregated data and information for planning and evaluation